2021
DOI: 10.3126/jcmsn.v17i2.33255
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Perception Regarding E- Learning during Covid-19 Lockdown Period

Abstract: Background and Objectives: Due to Covid-19 lockdown period undergraduate medical institutions across the country are moving towards e-learning for continuity of education. The purpose of this study is to determine the perceptions of students towards e-learning and to analyze medical students’ perception on e-learning vs. conventional learning. Materials and Method: This was a descriptive cross sectional study conducted by distributing an online semi-structured questionnaire consisting Likert scale to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…The initial paucity of literature on teachers' and students' experiences of OTL (by using mobile, Google Meet, YouTube, etc.) gradually gave way to new literature: Teachers pictured OTL both as fruitfully productive or participatory and not as eff ective as in physical classes whereas students took online classes as comparatively problematic and less eff ective than physical classes (Manandhar et al, 2021). More importantly, a few studies (Dangal & Bajracharya, 2020;Shrestha et al, 2022;Singh & Shrestha, 2021) reported that practices and aspects associated with OTL, following the pandemic-caused anxieties, negatively aff ected the mental wellbeing of students and teachers.…”
Section: Introductionmentioning
confidence: 99%
“…The initial paucity of literature on teachers' and students' experiences of OTL (by using mobile, Google Meet, YouTube, etc.) gradually gave way to new literature: Teachers pictured OTL both as fruitfully productive or participatory and not as eff ective as in physical classes whereas students took online classes as comparatively problematic and less eff ective than physical classes (Manandhar et al, 2021). More importantly, a few studies (Dangal & Bajracharya, 2020;Shrestha et al, 2022;Singh & Shrestha, 2021) reported that practices and aspects associated with OTL, following the pandemic-caused anxieties, negatively aff ected the mental wellbeing of students and teachers.…”
Section: Introductionmentioning
confidence: 99%